Practical Implementation of Blockchain Technology in Pharmaceutical Supply Chain Management - Rishi JP, Ramdas Bhat, Prateek Srivastava, M. Sundar Raj (International Journal of Intelligent Systems and Applications in Engineering, 2024)
This research examines the viable usage of blockchain innovation in pharmaceutical supply chain administration. Through an arrangement of tests and comparative examinations, the ponder assesses the effect of blockchain on key execution pointers such as traceability, straightforwardness, security, and proficiency. Results show noteworthy changes in traceability, with blockchain empowering real-time following of pharmaceutical items from fabricating to conveyance. Straightforwardness is improved through the utilisation of decentralized records, giving partners perceivability into supply chain operations. Security measures such as cryptographic hashing and computerized marks guarantee information keenness and ensure against extortion and unauthorized get to. Besides, the mechanization of forms by means of shrewd contracts leads to expanded proficiency in exchange preparation and compliance confirmation. The discoveries of this investigation highlight the transformative potential of blockchain innovation in revolutionizing pharmaceutical supply chain administration. Moving forward, it is basic for partners to address challenges such as adaptability and administrative compliance to completely realize the benefits of blockchain in guaranteeing the secure and effective conveyance of pharmaceutical items.